Urethral stone street - Atikeler, M.K.; Yüzgeç, V.; Geçit, I.; Ardiço?lu, A.; Yalçin, O. (My University, 2005)
[Abstract Not Available]
Keywords: Humans; Lithotripsy; Male; Middle Aged; Ureteral Calculi; Urinary Bladder Calculi; adult; article; bladder stone; case report; cystoscopy; dysuria; extracorporeal lithotripsy; hospital admission; human; male; pelvis pain syndrome; physical examination; urethra stone; urine retention; urography